2018
DOI: 10.3389/fnint.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneity and Temporal Order Judgments Are Coded Differently and Change With Age: An Event-Related Potential Study

Abstract: Multisensory integration is required for a number of daily living tasks where the inability to accurately identify simultaneity and temporality of multisensory events results in errors in judgment leading to poor decision-making and dangerous behavior. Previously, our lab discovered that older adults exhibited impaired timing of audiovisual events, particularly when making temporal order judgments (TOJs). Simultaneity judgments (SJs), however, were preserved across the lifespan. Here, we investigate the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…Previous studies reported a number of changes in multisensory perception with age. For example, OA seemed to benefit more from multisensory compared to unisensory information during speeded detections (Laurienti et al, 2006;Mahoney et al, 2014;Zou et al, 2017), had longer temporal binding windows (Basharat et al, 2018;Chan et al, 2014b;DeLoss et al, 2013;Hay-McCutcheon et al, 2009;Noel et al, 2016), experienced increased difficulty to segregate multisensory stimuli (Setti et al, 2011), and more strongly fused audio-visual speech (Sekiyama et al, 2014;Setti et al, 2013). Contrasting this view, recent work suggests that healthy young and aging brains may follow similar computational rules when combining multisensory information (Billino & Drewing, 2018;Campos et al, 2018;Cressman et al, 2010;Jones et al, 2019), except possibly that the OA may take longer to respond as a result of agerelated slowness (Jones et al, 2019.…”
Section: Changes In Within-trial Multisensory Integration With Agementioning
confidence: 97%
“…Previous studies reported a number of changes in multisensory perception with age. For example, OA seemed to benefit more from multisensory compared to unisensory information during speeded detections (Laurienti et al, 2006;Mahoney et al, 2014;Zou et al, 2017), had longer temporal binding windows (Basharat et al, 2018;Chan et al, 2014b;DeLoss et al, 2013;Hay-McCutcheon et al, 2009;Noel et al, 2016), experienced increased difficulty to segregate multisensory stimuli (Setti et al, 2011), and more strongly fused audio-visual speech (Sekiyama et al, 2014;Setti et al, 2013). Contrasting this view, recent work suggests that healthy young and aging brains may follow similar computational rules when combining multisensory information (Billino & Drewing, 2018;Campos et al, 2018;Cressman et al, 2010;Jones et al, 2019), except possibly that the OA may take longer to respond as a result of agerelated slowness (Jones et al, 2019.…”
Section: Changes In Within-trial Multisensory Integration With Agementioning
confidence: 97%
“…For instance, a broad network of cortical structures has been implicated in AV timing perception 17 , as has activity with a surprisingly short latency post stimulation (~45 ms) 18,19 . Evidence also suggests that different timing decisions rely on different substrates 20 . Our focus on the precision of AV timing judgments extends the scope of these investigations, and they may have more general implications, for precision in other sensory contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is often accompanied with age-related changes in sensory (e.g., hearing impairment) and cognitive capabilities (e.g., working memory, processing speed), both of which can affect mechanisms of multisensory integration. Multisensory integration is considered to be closely linked to the ability to conduct activities of daily living, especially for older individuals (de Dieuleveult et al, 2017;Basharat et al, 2018; and see, for example, for balance and falling, Mahoney et al, 2014;Setti et al, 2011). Therefore, the search for practical, applicable, and effective tests for multisensory integration, which can be implemented in clinical settings, continues (e.g., de Dieuleveult et al, 2019).…”
Section: Clinical Relevancementioning
confidence: 99%